Motivational Climate in the Classroom Factorial and Convergent Validity Evidence of the Need-Supportive Behaviors Scale With Health Science Students - Gucciardi, Daniel; Chen, Joseph Weixian; Gibson, W.; Ntoumanis, Nikos; Ng, Leo (Hogrefe Publishing, 2019)
© 2019 Hogrefe Publishing. Adaptive motivation is central to positive functioning. Social agents such as teachers play a significant role in shaping the motivation of people with whom they interact by satisfying or thwarting their psychological needs of autonomy, competence, and relatedness. The development and validation of tools that assess the types of behaviors social agents adopt to satisfy these psychological needs are important agenda items for substantive and applied researchers. In this study, we examined factorial and convergent validity evidence of a need support scale adapted from the physical education context for use in tertiary settings with health science students. Factor analyses of responses from 290 health science students indicated that need-supportive behaviors are best captured by one latent factor, rather than the a priori 4-factor structure designed to capture needs for autonomy, relatedness, and competence. Regression analyses supported the convergent validity of the unidimensional structure, such that students who perceived higher levels of need-supportive behaviors from their tutor reported higher levels of behavioral engagement, and experiences of vitality and learning. Validation of a scale that assesses need-supportive behaviors within a health science context provides researchers with a tool to employ in future research that aims to investigate the antecedents and outcomes of such behaviors, as well as the effects of interventions designed to equip educators with the skills, motivation, and knowledge to employ successfully such behaviors.